72. A novel ATP7A-related phenotype with distal motor neuropathy and autonomic dysfunction: Case report of two sibs. Issue 12 (December 2017) - Sette, E.; Simioni, V.; Capone, J.G.; Bigoni, S.; Rispoli, V.; De Grandis, D.; Donadio, V.; Liguori, R.; Ferlini, A.; Gualandi, F.; Tugnoli, V.
Abstract : To describe a novel ATP7A-related phenotype associating distal motor neuropathy and autonomic dysfunction. Next-generation sequencing analysis of a lower-motor neuron diseases gene panel was performed in two sibs presenting with distal motor neuropathy plus an autonomic dysfunction, which main manifestation was retrograde ejaculation and chronic diarrhea. Probands were subjected to dysmorphological, neurological, biochemical and electrophysiological evaluation including nerve conduction studies, sympathetic skin responses (SSR), cutaneous flowmetry (CF), Quantitative Sensory Testing (QST) and local skin axonal reflexes (AR). We also performed a skin biopsy. A novel pathogenic missense mutation (p.A991D) was identified in the X-linked ATP7A gene, segregating in both brother and inherited from the healthy mother. Biochemical studies showed reduced serum copper and ceruloplasmin. Clinical and neurophysiological evaluation documented large and small fibers neuropathy with severe autonomic involvement. Mutations in the ATP7A gene have been classically associated to the severe infantile neurodegenerative Menkes disease (MD) and the Occipital Horn Syndrome (OHS). In 2010, ATP7A missense mutations were identified in two families with a pure axonal distal motor neuropathy (dHMN-SMAX3). The novel phenotype we describe bridges dHMN to MD-OHS and highlights that the full spectrum of ATP7A-related diseases represents a clinical continuum with no clear-cut genotype-phenotype correlations.